A Key Research Case for Promoting Education for Sustainable development: The Case of Okayama, Japan - He, Xinyuan (International Journal of Social Sciences and Public Administration, 2024)
This paper explores the productive efforts of Okayama City, Japan, in advancing education for sustainable development (ESD). Focusing on two significant initiatives, the Marine Conservation Education Program and RCE Okayama, the paper explores how these programs integrate formal, non-formal, and informal education to foster sustainable practices. The Marine Conservation Education Program, a collaboration between schools and local fishermen, involves experiential learning to instill marine conservation principles among students, yielding significant shifts in their attitudes towards ocean protection. RCE Okayama, recognized globally, collaborates with various organizations to promote ESD within the community, offering programs and training to enhance understanding and implementation of sustainable practices. The paper emphasizes the synergy of formal and non-formal education, highlighting the broader impacts of Okayama's ESD efforts on developing a sustainable society.